Pengaruh Aset dan Manajemen Inventory terhadap Manajemen Laba - RUSLI, ISKANDAR (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
This research aimed to study the inuence of the values of quick ratio, debt ratio, return-on-assets, inventory turnover, and assets turnover toward the net prot before tax in the food and beverage industries in Jakarta Stock Exchange in the year 2002-2006. The approach used is qualitative approach with double regression. The result shows that the variables of quick ratio, inventory turnover, assets turnover, return-on-assets signicantly inuence the prot before tax. The use of nancial ratio is proved to be benecial for prot management.